2002
DOI: 10.1097/00005650-200212000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Recognition of Drug Interactions

Abstract: Automated drug interaction alerts have the potential to dramatically increase clinicians' recognition of selected drug interactions. However, perceived poor specificity of drug alerts may be an important obstacle to efficient utilization of information and may impede the ability of such alerts to improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(64 citation statements)
references
References 25 publications
0
61
1
2
Order By: Relevance
“…16,17 In the study by Weingart et al, 11 physician reviewers judged onethird of generated alerts to be inappropriate. Similarly, our previous experience with drug-allergy alerts highlighted that the vast majority of allergy alert overrides were clinically appropriate and did not lead to adverse drug events.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In the study by Weingart et al, 11 physician reviewers judged onethird of generated alerts to be inappropriate. Similarly, our previous experience with drug-allergy alerts highlighted that the vast majority of allergy alert overrides were clinically appropriate and did not lead to adverse drug events.…”
Section: Discussionmentioning
confidence: 99%
“…Too many unwanted alerts (Robertson, et al, 2011); (Glassman, Simon, Belperio, & Lanto, 2002); (Tierney, et al, 2005); (Murray, et al, 2004) Poor system design (Robertson, et al, 2011 …”
Section: List Of Barriers Papersmentioning
confidence: 99%
“…Results from a survey of prescribers revealed that specialists were less likely to identify interactions than general physicians [19]. Another study found that younger clinicians identified more potential interactions than older clinicians due to possible reasons like aged-related memory loss and the lack of continuing medical education on potential DDIs [20]. Conclusions from this study reflect the need to alert oncologists about potentially interacting AED-oral ACD pairs when they are being co-prescribed.…”
Section: Discussionmentioning
confidence: 96%